2016
DOI: 10.1080/00063657.2016.1180341
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Black-backed GullsLarus fuscusthriving on a non-marine diet

Abstract: Capsule: Lesser Black-backed Gulls Larus fuscus breeding 30 km from the coast in the Netherlands focussed entirely on terrestrial food sources and reached relatively high breeding success. Aim: To gain insight in the foraging ecology, habitat use and breeding performance of inlandbreeding Lesser Black-backed Gulls. Methods: We received data from seven birds fitted with global positioning system (GPS) loggers. The colony was frequently visited to collect pellets and boluses and to monitor reproductive success, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Doñana includes up to 37,000 ha of ricefields (Green, Bustamante, Janss, Fernández‐Zamudio, & Díaz‐Paniagua, ), where bird numbers peak at the time of rice harvest, with many of the same birds switching to natural wetlands in Doñana and other parts of Andalusia during the rest of the wintering period (Bouten, Baaij, Shamoun‐Baranes, & Camphuysen, ; Rendón et al., ). Gulls (Laridae) are opportunistic and omnivorous birds that often feed on alien crayfish (Christel, Navarro, del Castillo, Cama, & Ferrer, ; Gyimesi et al., ; Mortimer et al., ). Equally, gulls also consume grains and other seeds and can be important vectors for dispersal of native and alien plants (Green, ; Green et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Doñana includes up to 37,000 ha of ricefields (Green, Bustamante, Janss, Fernández‐Zamudio, & Díaz‐Paniagua, ), where bird numbers peak at the time of rice harvest, with many of the same birds switching to natural wetlands in Doñana and other parts of Andalusia during the rest of the wintering period (Bouten, Baaij, Shamoun‐Baranes, & Camphuysen, ; Rendón et al., ). Gulls (Laridae) are opportunistic and omnivorous birds that often feed on alien crayfish (Christel, Navarro, del Castillo, Cama, & Ferrer, ; Gyimesi et al., ; Mortimer et al., ). Equally, gulls also consume grains and other seeds and can be important vectors for dispersal of native and alien plants (Green, ; Green et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For central placed foragers who visit multiple destinations in a trip, feed on a wide array of resources and often behave opportunistically, exploratory behaviours in relation to resource distribution are expected to play a role in movement decisions 47 . Availability of lift may then make more distant sites more attractive or accessible and help facilitate the increased amounts of terrestrial foraging that are being observed in these species 36,48 . In addition, the role of landscape features in providing cues for animal navigation have been widely studied as a means by which routes are formed 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the study colony at Zeebrugge was mainly founded by immigrants originating from nearby coastal colonies along the Southern North Sea that likely exploited fishery discards (Seys et al, 1998), and can thus be expected to contain a large number of marine-specialist individuals. The extent to which local adaptation and social learning affect the cost of provisioning chicks with terrestrial food should be further assessed by studying the relationships here described in populations that are mostly reliant on terrestrial food sources (e.g., Coulson & Coulson, 2008; Gyimesi et al, 2016), where specialists in different terrestrial foraging modes may be found. Moreover, early diet could affect an individual’s proficiency at exploiting a particular foraging niche through ontogenetic effects on physiological and morphological traits (Oudman et al, 2016), further affecting the cost-to-benefit ratio of individual foraging strategies.…”
Section: Discussionmentioning
confidence: 99%